KESIAPSIAGAAN BENCANA GEMPA BUMI DALAM KEPERAWATAN: TINJAUAN PENELITIAN - Cahyo, Firman Dwi; Ihsan, Farly; Roulita, Roulita; Wijayanti, Nunik; Mirwanti, Ristina (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2023)
Background: In the face of disasters, preparedness is the key to safety. This shows that there is a need for a preparedness plan in the field of disaster nursing, especially earthquakes so that it can minimize losses that will occur. Objective: This review aims to improve a practical understanding of earthquake disaster preparedness. Method: Search articles using keywords in the Pubmed, CINAHL, Science Direct, and Official Website databases with the criteria for articles using Indonesian or English, full text available published between 2011 and 2021. The search results obtained 667 articles and obtained 7 relevant articles. Result: Earthquake preparedness plans need to be anticipated starting from the family structure which emphasizes that each individual and family personnel have a role in earthquake disaster preparedness, as well as in community and community settings which emphasize cooperation, disaster mitigation, and post-disaster recovery plans. Conclusion: Understanding, awareness, and ability related to earthquake disaster preparedness for individuals, families and the community needs to be improved through health education, training, and disaster simulations and needs to be given to the community including disaster awareness, situation and disaster risk analysis, disaster preparedness strategies, prevention, and what to do in the event of a disaster, disaster communication and triage as well as first aid during a disaster and basic life support.